Music's Impact on Physical Performance: A Study of Individuals Engaging in Fitness Activities - Serkan ÇELİK; İbrahim DALBUDAK (ümit doğan üstün, 2023)
This study aims to investigate the influence of music on individuals engaging in fitness activities at fitness centers in Izmir. A total of 249 individuals willingly participated in the study. The study utilized the personal information form and the impact of music on sportive activities scale, which were designed by Karayol and Turhan (2020), as data collection instruments. The scale comprises 18 items and is divided into 3 sub-dimensions, each measured using a 5-point Likert scale. The data was analyzed using the SPSS software package. The statistical procedures used in the data analysis included the "Independent samples t-test" and "One-way analysis of variance (ANOVA)" tests to examine intergroup differences. Additionally, the "Tukey Post Hoc" test was employed. According to the analyzed results, the research revealed a notable disparity in the sub-dimensions of the influence of music on age and overall total scores during physical activities (p<0.05). The study found that there was no statistically significant difference in the effect of music on the physical strength and performance of persons during sports activities based on their gender (p>0.05). However, there was a statistically significant difference in other aspects and overall scores (p<0.05). The impact of music on motivation during sportive activity varied significantly based on people' marital status (p<0.05). However, there was no significant difference in other sub-dimensions and overall total scores based on marital status (p>0.05). A statistically significant difference was observed in the sub-dimensions of the influence of music on income level and overall total scores during physical activities (p<0.05). The study found that there was no statistically significant difference in the effect of music on the motivation and physical strength and performance of individuals during sports activities, based on their regular participation in sports (p>0.05). However, a significant difference was observed in the overall scores of psychological practice and the general scale (p<0.05). Based on the research findings, it can be concluded that music has a substantial influence on persons who engage in fitness activities during sports. It is advisable to assess the influence of music on various sports disciplines as well as on individuals in non-sporting domains. This holds significance in assessing the influence of music on individuals.